Unfair trading practices in the agri-food chain - Vázquez Ruano, Trinidad (Przegląd Prawa Rolnego, 2024)
One of the objectives of the Common Agricultural Policy is to improve competition in the agri-food sector. Modifications to this policy have focused on food quality, environmental protection and improving trade relations. Similarly, the regulatory proposals of the European Commission between 2021 and 2027 aim to achieve a sustainable agricultural sector that promotes competitiveness. In this article, the commercial practices of traders in the agri-food market and the actors that are part of the distribution chain of these products are examined. Particular attention is given to unfair behaviour that affects the interests of competitors, consumers and other participating actors.